2004
DOI: 10.1128/jb.186.3.730-739.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Mutant Form of the Neisseria gonorrhoeae Pilus Secretin Protein PilQ Allows Increased Entry of Heme and Antimicrobial Compounds

Abstract: A spontaneous point mutation in pilQ (pilQ1) resulted in phenotypic suppression of a hemoglobin (Hb) receptor mutant (hpuAB mutant), allowing gonococci to grow on Hb as the sole source of iron. PilQ, formerly designated OMP-MC, is a member of the secretin family of proteins located in the outer membrane and is required for pilus biogenesis. The pilQ1 mutant also showed decreased piliation and transformation efficiency. Insertional inactivation of pilQ1 resulted in the loss of the Hb utilization phenotype and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 53 publications
(70 reference statements)
2
51
0
Order By: Relevance
“…As mentioned previously, two classes of mutants have been isolated in Neisseria gonorrhoeae that were more susceptible to both heme and PPIX. In addition to these porphyrin sensitivities, both classes of mutants were hypersensitive to other HAs as well (3). Subsequently, tests similar to those carried out by Chen et al (3) demonstrated that ght mutants are also hypersensitive to HAs such as Triton X-100 and rifampin in addition to heme and PPIX.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…As mentioned previously, two classes of mutants have been isolated in Neisseria gonorrhoeae that were more susceptible to both heme and PPIX. In addition to these porphyrin sensitivities, both classes of mutants were hypersensitive to other HAs as well (3). Subsequently, tests similar to those carried out by Chen et al (3) demonstrated that ght mutants are also hypersensitive to HAs such as Triton X-100 and rifampin in addition to heme and PPIX.…”
Section: Discussionmentioning
confidence: 59%
“…Efforts to transfer the nonpolar ght::Kan r construct from the meningococci to the gonococci to better understand HA hypersensitivity and ght's effects on piliation proved unsuccessful (data not presented), suggesting that ght may be an essential gene in the gonococci. Moreover, a meningococcal strain harboring mutations in HpuB and HmbR is not able to grow in the presence of hemoglobin as a sole iron source under the same conditions described by Chen et al for their gonococcal mutants (3).…”
Section: Discussionmentioning
confidence: 97%
“…The channel function of neisserial secretins has been assessed to some extent (Chen et al, 2004;Zhao et al, 2005). Meningococcal PilQ can behave as a gated channel and regulator of transmembrane flux control.…”
Section: Discussionmentioning
confidence: 99%
“…HpuA and HpuB form a functional complex, and both are required for the utilization of hemoglobin and hemoglobin-haptoglobin as nutrient iron sources (59,61). Coincidentally, a spontaneous point mutation in Neisseria gonorrhoeae pilQ (pilQ1) suppresses the mutant hpuAB phenotype (16). PilQ forms a channel in the outer membrane and is required for pilus biogenesis, but its mutant form allows the entry of heme and various antimicrobial compounds with a TonB-independent, PilT-dependent mechanism (16).…”
Section: Heme Sources Exploited By Bacterial Pathogensmentioning
confidence: 99%